2020
DOI: 10.21203/rs.3.rs-22268/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cariogenic and erosive potential of liquid oral pediatric medicines of long-term use for children: an in vitro analysis

Abstract: Background Liquid oral pediatric medicines (LOPM) contain sucrose and glucose and can have a low pH; their chronic administration may increase the risk for dental caries and erosion in children. The aim of this study was to determine sucrose and glucose concentrations, and pH of LOPMs of long-term use by children. Methods A cross sectional survey was conducted among 95/381 pharmacies to assess the most commonly prescribed LOPM by pharmacists in North Jordan, yielding 42 medicines which were analyzed for sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
2
3
Order By: Relevance
“… 2 , 33 However, antimicrobials in liquid oral medications showed higher pH. 3 , 35 Analgesics in our study showed the highest pH (6.71), which was more than that reported in LOMs. 13 , 15 , 35 , 36 Antiemetics had a similar (6.03) pH as compared to Maguire et al and Arora et al (6.28 and 6.04, respectively).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“… 2 , 33 However, antimicrobials in liquid oral medications showed higher pH. 3 , 35 Analgesics in our study showed the highest pH (6.71), which was more than that reported in LOMs. 13 , 15 , 35 , 36 Antiemetics had a similar (6.03) pH as compared to Maguire et al and Arora et al (6.28 and 6.04, respectively).…”
Section: Discussioncontrasting
confidence: 52%
“…2,33 However, antimicrobials in liquid oral medications showed higher pH. 3,35 Analgesics in our study showed the highest pH (6.71), which was more than that reported in LOMs. 13,15,35,36 26,[33][34][35] There was no significant difference in the pH between the short-term and the long-term medication, similar to the previous study.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…2,33 However, antimicrobials in liquid oral medications showed higher pH (6.4 and 6.36). 3,35 Analgesics in our study showed the highest pH (6.71), which was more than that reported in LOMs. 13,15,35,36 26,[33][34][35] There was no significant difference in the pH between the short-term and the long-term medication, similar to the previous study.…”
Section: Discussioncontrasting
confidence: 49%
“…2 Many liquid oral medications (LOM) contain readily available sugars like sucrose and glucose. 3 The requirement for easily adjustable dosage forms is one of the most frequent issues in pediatric pharmacology. 4 This issue has long been resolved by the development and use of liquid preparations.…”
Section: Introductionmentioning
confidence: 99%